Fluctuación poblacional de adultos de Sagalassa valida Walker (Lepidoptera: Brachodidae) en Stachytarpheta cayennensis (Rich.) Vahl - Zegarra-Arteaga, Oliviño (2024)
Adults of Sagalassa valida Walker (Lepidoptera: Brachodidae) are attracted to the nectars of weed flowers, including Starchytarpheta cayennensis. However, when they are larvae, they damage the roots and consume them completely. The objectives of this work were to determine the population fluctuation of adults of Sagalassa valida, the relationship and sex ratio. The research was carried out in the province of Tocache from January 2015 to February 2016, in three oil palm plots in which verbena was planted. Verbena was planted on two dates: the first in January and the second in May, the purpose of which was to flower throughout the year. Once in flower, adults were captured using an entomological net, making 2 passes through each verbena plant, from 7:00 to 8:30. and from 4:30 p.m. to 6:00 p.m., the adults captured daily were recorded. The results indicate that the population increases during May, with its highest peak in August to September due to low rainfall and variations in temperature and humidity, decreasing from October to a lower level in February, due to increased rainfall.